2014
DOI: 10.1364/ol.39.000493
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared fiber lasers at and beyond 35 μm using dual-wavelength pumping

Abstract: We report the first, to the best of our knowledge, erbium-doped zirconium-fluoride-based glass fiber laser operating well beyond 3 μm with significant power. This fiber laser achieved 260 mW in CW at room temperature. The use of two different wavelength pump sources allows us to take advantage of the long-lived excited states that would normally cause a bottleneck, and this enables maximum incident optical-to-optical efficiency of 16% with respect to the total incident pump power. Both output power and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 169 publications
(85 citation statements)
references
References 17 publications
(25 reference statements)
1
84
0
Order By: Relevance
“…The impact of this ET process was reduced in recent work [3,4] that used lower doping densities and double clad fibers which resulted in lower population densities at the 4 F 9/2 and 4 I 11/2 states. The combination of this and increased P 1 power removed the laser power saturation that was observed in our earlier work [2].…”
supporting
confidence: 50%
See 1 more Smart Citation
“…The impact of this ET process was reduced in recent work [3,4] that used lower doping densities and double clad fibers which resulted in lower population densities at the 4 F 9/2 and 4 I 11/2 states. The combination of this and increased P 1 power removed the laser power saturation that was observed in our earlier work [2].…”
supporting
confidence: 50%
“…In a previous publication we demonstrated that dual wavelength pumping (DWP) could significantly increase the efficiency of erbium doped ZBLAN glass fiber lasers that operate on the 3.5 µm transition. We reported a continuous-wave (CW) output power in excess of 250 mW which was the first room temperature rare-earth doped fiber laser to produce more than 10 mW well beyond 3 µm [2]. Recently two groups have reported over 1 W of power at 3.5 µm using this approach [3,4].…”
Section: Introductionmentioning
confidence: 95%
“…This technique offers the additional benefit of using infrared pump wavelengths that are more readily available at higher powers than the visible sources required for direct ground state pumping. Our initial work demonstrated this concept on the 4 F 9/2 → 4 I 9/2 transition in erbium [21], [25], [26]. Our first demonstration of mid-infrared DWP laser significantly surpassed the 10 mW barrier, achieved a slope efficiency of 25 % and brought the 3.5 µm Er 3+ transition onto the trend line shown in Fig.…”
Section: Mid−infrared Emission Wavelength (µM) Output Power (W)mentioning
confidence: 95%
“…Figure 2 schematically shows the energy level diagram of the lowest five levels of the erbium ion, the two lasing transitions relevant to this work and the two pump wavelengths. In an earlier work [9], we showed that DWP is an efficient means of generating emissions from the 3.5 μm band transition of erbium. A population of ions is established in the metastable 4 I 11∕2 level by the absorption of P 1 photons on the 974 to 985 nm ground state absorption band.…”
mentioning
confidence: 94%
“…After this review was written, a Raman fiber laser produced 50 mW at 3.34 μm [8]. Recently, we introduced an optical pumping method that allows the use of mature, well developed near-infrared sources to excite high lying energy levels of rare earth ions [9]. In this work, we demonstrated that dual wavelength pumping (DWP) could significantly increase the efficiency of erbium doped ZBLAN glass fiber lasers that operate on the 4 F 9∕2 → 4 I 9∕2 transition at 3.5 μm.…”
mentioning
confidence: 99%